Economics for business - Begg, David K. H. (McGraw-Hill Education, 2007)
Offering an integrative approach, this book uses references to real-world examples to demonstrate how modern economics can illuminate the problems that businesses face every day. Thus, the text emphasizes economic reasoning as the solution to business problems